PEMBENTUKAN KARAKTER DI PERGURUAN PENCAK SILAT BELADIRI TANGAN KOSONG MERPATI PUTIH (Faculty of Social Science, Universitas Negeri Semarang, 2015)
This research raised about the character building in Perguruan Pencak Siat Beladiri Taangan Kosong Merpati Putih, this research using qualitative-descriptive research methods. Data source on this study using the primary and secondary data, which has the authors got from data collection techniques consist of observation form, interviews, and documentation from 5 January to 31 January. The results of this research show that there are three stages on the character building in Silat Merpati Putih, namely in-put, the efforts of character building, and successfully formed character by Silat Merpati Putih. In-put stage used as a pre-test to the prospective members of Silat Merpati Putih. Furthermore, there were eight efforts performed by Silat Merpati Putih on the character building. Based on the results of the author's research, there are seven main characters and 13 characters that go with it. There are three obstacles that have been faced by Silat Merpati Putih in building the character of it's members, consist ofthe members reason to join Silat merpati Putih, based on the family background, and teammates.